Recent Progress in Electrically Conductive and Thermally Conductive Lubricants: A Critical Review - Bayazid Bustami; Md Mahfuzur Rahman; Mst. Jeba Shazida; Mohaiminul Islam; Mahmudul Hasan Rohan; Shakhawat Hossain; Alam S. M. Nur; Hammad Younes (Lubricants, 2023)
Electrically as well as thermally conductive lubricants have drawn considerable attention and are an emerging research topic because they have unique advantages and advanced lubrication performance over traditional lubricants such as corrosion protection and efficient heat dissipation. For instance, some components of electric vehicles (EVs) such as bearings, seals, pads and gears require conductive lubricants to avoid premature failure and electromagnetic interference (EMI) problems due to induced shaft voltages and currents. This review provides a comprehensive overview of the recent developments in conductive lubricants. The review focuses on the important aspects to enhance the thermal and electrical conductivities as well as the tribological behavior (COF, and wear rate) of conductive solid, semisolid, and liquid lubricants. The lubricants that are electrically and thermally conductive with superior tribological performances have been identified through extensive literature review and presented in tabular form. This review summarizes the effect of various additives used to improve the conductive properties of the lubricants, such as polyalphaolefin oil, hydraulic oil, paraffin oil, and mineral oil. Furthermore, the review discusses the lubricating mechanism of conductive solid and liquid lubricants to facilitate a deeper understanding. Finally, the future perspectives and the research directions for conductive lubricants are also addressed.